Effects of hot air drying on muscle quality, volatile flavor compounds, and lipid profiles in sword prawn (Parapenaeopsis hardwickii) based on physicochemical, GC-IMS, and UHPLC-MS/MS-based lipidomics analysis - Wenxiong Zheng; Ronglin Yang; Shanshan Shui; Feili Zhan; Lucheng Wang; Rui Lu; Soottawat Benjakul; Bin Zhang (Food Chemistry: X)
The changes in physicochemical index, volatile flavor, and lipid profiles in Parapenaeopsis hardwickii during hot air drying were studied. As drying time progressed, the L*, hardness, chewiness, gumminess, peroxide value (PV), and thiobarbituric acid reactive substances (TBARS) of P. hardwickii increased gradually, while the a* and b* values first increased and then decreased, and springness decreased progressively. Hot air drying caused the myofibrils to widen and become disordered. Additionally, 5 volatile organic compounds (VOCs) and 30 lipid molecules were identified as key differential markers to the flavor and lipid profiles, respectively. Pearson correlation analysis revealed a strong relationship between shrimp muscle quality and lipid oxidation, with lipid oxidation promoting the development of characteristic flavors and an increase in their levels. Lysophosphatidylethanolamine (LPE), specifically 20:2e, 18:2e, 18:1e, and 16:1e, were identified as primary lipids contributing to the formation of these characteristic flavor differential markers during hot air drying. Glycerophospholipids (GPs) containing LPE as key substrates driving flavor formation in shrimp during hot air drying. This study offers a comprehensive theoretical framework for controlling flavor quality in shrimp muscle during hot air drying.